COVID-19 Vaccination Induced Neurological Complications; A Systematic Literature Review - Paul Wesley Thompson (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Vaccination against COVID-19 is proved successful in reducing the transmission of disease globally along with reducing the severity of disease but vaccine associated adverse effects (VAERS) questions the safety profile of COVID-19 vaccines especially the serious neurological adverse effects that are responsible for post-vaccination mortalities globally. Aim: To review the neurological adverse effects of COVID-19 vaccines and identify their possible pathophysiology Method: The literature search was conducted by two researchers. The database of Google Scholar was used to search relevant literature. All the articles published between 1st Jan, 2018 to 1st Jan 2022 were screened for inclusion and exclusion criteria. Results: The search strategy resulted in 278 articles of which, 1duplicates were removed and 277 articles were screened according to inclusion exclusion criteria, 103 articles were excluded and a total of 20 articles were included in review of which there were 17 case reports,1 observational studies, 1 case series and 1 case-control study. Conclusion: The findings of review provide a deep insight of neurological complications that can occur in individuals after receiving COVID-19 vaccination and the clinicians should be conscious while dealing with a patient with new-onset neurological symptoms after vaccination against COVID-19 unless a causal association is developed between the vaccine and serious neurological adverse events by future researches. Keywords: COVID-19, Post-vaccination, Neurological Complications, Vaccine Associated Adverse events, Acute Ischemic Stroke and GBS